Transient Elastography in the Diagnosis of Pediatric Non-alcoholic Fatty Liver Disease and Its Subtypes - Yang, Lin; Zhu, Yafei; Zhou, Lu; Yin, Huimei; Lin, Yan; Wu, Guangsheng (Frontiers in Pediatrics, 2022)
Abstract: (1) Objective: To study the diagnosis efficacy of controlled at-tenuation parameters(CAP) and liver stiffness measurement(LSM) in the liver ultrasound elastography for the diagnosis of nonalcoholic fatty liver disease(NAFLD) and its subtypes in children with obesity; (2) Methods: Retrospectively analyze the children with obesity in the Childhood Obes-ity Clinic of the Affiliated Hospital of Hangzhou Normal University from July 2020 to March 2021. The correlation between clinical data and NAFLD subtypes was analyzed, and relevant clinical data were incorpo-rated into the receiver operating characteristic curve for diagnosis and prediction. (3) Results: 120 children aged between 6.1 and 17.8 years,with 70 boys (58.33%),50 girls (41.67%)and a ratio of 1.4:1, were enrolled in this retrospective study. CAP and LSM were correlated in all subtypes of NAFLD. It was significant for the diagnosis of NAFLD in children with obesity when CAP>258.00dB/m and LSM>4.65kPa. It was also significant for the diagnosis of NASH when CAP>276.00dB/m and LSM>5.15kPa,while it was less significant for the diagnosis of NAFLD in children with obesity; (4) Conclusions: CAP and LSM have diagnostic ef-ficacy for NAFLD and its subtypes in children with obesity, with CAP>258.00dB/m and LSM>4.65kPa being the optimal predictive values for NAFLD in children with obesity, and CAP>276.00dB/m and LSM>5.15kPa being the optimal predictive values for NASH in children with obesity.